2008
DOI: 10.1007/s11746-008-1304-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Fatty Acid Compositions, Oil Content and Oil Yield in a Germplasm Collection of Sesame (Sesamum indicum L.)

Abstract: The variation in oil content, oil yield and fatty acid compositions of 103 sesame landraces was investigated. The landraces varied widely in their oil quantity and quality. The oil content varied between 41.3 and 62.7%, the average being 53.3%. The percentage content of linoleic, oleic, palmitic and stearic acids in the seed oil ranged between 40.7-49.3, 29.3-41.4, 8.0-10.3 and 2.1-4.8%, respectively. Linolenic and arachidic acids were the minor constituents of the sesame oil. Linoleic and oleic acids were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
90
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 21 publications
12
90
2
1
Order By: Relevance
“…Oil contents of sesame varieties ranged from 47.9-54.7% in Soxhlet method and from 31.1-42.8% in cold press method. In this manner, results of this study are similar to the findings of Uzun et al (2008) who reported oil content of 103 Turkish sesame landraces ranged from 41.2-62.7%. Similar results were reported by Asghar & Majeed (2013) and Nzikou et al (2009).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Oil contents of sesame varieties ranged from 47.9-54.7% in Soxhlet method and from 31.1-42.8% in cold press method. In this manner, results of this study are similar to the findings of Uzun et al (2008) who reported oil content of 103 Turkish sesame landraces ranged from 41.2-62.7%. Similar results were reported by Asghar & Majeed (2013) and Nzikou et al (2009).…”
Section: Resultssupporting
confidence: 91%
“…Oleic and linoleicacids are the major fatty acids of sesame oil (Arslan et al, 2007;Uzun et al, 2008), and they are found to be present in large proportion in the oils of all genotypes. Oleic acid content of sesame oil ranged from 37.15 to 41.67%.…”
Section: Resultsmentioning
confidence: 99%
“…In other crops such as Sesamun indicum L (Were et al 2006), Brassica napus L (Zhao et al 2008), or Zea mays (Yang et al 2010), this negative correlation is frequently justified as pleiotropic effects of single genes or closely linked genes controlling different traits (Yang et al 2010). The negative correlation between C18:2 and C18:1 had been reported in Sesamum indicum L (Uzun et al 2008), maize (Yang et al 2010), and Arachis hypogaea L. (Sarvamangala et al 2011). However, estimates of genetic (additive) and pure environmental correlations cannot be precisely estimated on our single cross where all offsprings have the same kinship degree.…”
Section: Fatty Acid Compositionmentioning
confidence: 98%
“…Thus, the objectives of our study were to determine the interactive efficiency of Ca 2+ application both in the metabolism of lipids in sesame (Sesamum indicum L.) and in plant tolerance to Cd stress. Sesame (S. indicum L.), an herbaceous annual plant, was chosen for this study because of its high content of oil and polyunsaturated fatty acids (up to 90%), which include linoleic, oleic, stearic and palmitic acids (Uzun et al 2008). …”
Section: Introductionmentioning
confidence: 99%